Undergraduate Accounting Students' Perceptions of Accounting Careers in Indonesia on the Accounting Profession Approach - Ine Saraswati; Annagayatul Husna; Siti Nur Hadiyati (PT FORMOSA CENDEKIA GLOBAL, 2024)
Public Accounting is one of the leading courses and programs in Indonesia. However, current datashow that the number of accounting professionals in Indonesia is very small compared to the population.Therefore, it is necessary to make students aware of bookkeeping. The purpose of this researchis to find out the influence of accounting students' opinions about the accounting professionon their interest in the accounting profession. A sample of accounting students in the 6th and8th semesters of the accounting curriculum in Swadaya Gunung Jat University were used as respondents.Research results show that the career choices of undergraduate studentsare more influenced by student interest variables and accounting majors and hard and soft skillsdo not seem to affect career choice of undergraduate students in accounting.